Antitrypanosomal activity of hydromethanol extract of leaves of Cymbopogon citratus and seeds of Lepidium sativum: in-vivo mice model - Ayechew Yetayeh Emiru; Eyasu Makonnen; Fikru Regassa; Fekadu Regassa; Takele Beyene Tufa (BMC, 2021)
Abstract Background Trypanosomiasis is one of the neglected tropical diseases of both humans and animals which decreases their productivity and causes death in the worst scenario. Unavailability of vaccines, the low therapeutic index of trypanocidal drugs, and the development of resistance lead to the need for research focused on developing alternative treatment options especially from medicinal plants. The present study was aimed to investigate antitrypanosomal activities of leaves of Cymbopogon citratus and seeds of Lepidium sativum in in-vivo mice model. Methods The plant extracts were prepared by maceration using 80% methanol and reconstituted with 10% dimethyl sulfoxide (DMSO) to have the desired concentration. The test doses were adjusted to 100, 200 and 400 mg/kg based on the toxicity profile. The plants extracts were administered to the respective groups of mice after the 12th day of field isolate T. congolense inoculation for seven consecutive days. The level of parasitemia, bodyweight, packed cell volume (PCV), and differential white blood cell counts were measured. Results The in -vivo test results revealed that both plant extracts had dose-dependent antitrypanosomal activity. Both crude extracts showed a significant reduction in parasite load (P < 0.05), increased or prevent the fall of PCV value (P < 0.05), decreased lymphocytosis and increased neutrophil counts (p < 0.05) and improved bodyweight but significant bodyweight increment (P < 0.05) was observed only in C. citratus treated mice compared to the negative and positive controls. Conclusion The present study concluded that the crude extracts of leaves of C. citratus and seeds of L. sativum had antitrypanosomal effects. Both plants extracts reduced parasitemia level, prevented anemia and improved bodyweight of treated mice. Comparative results from all tested parameters showed that the best activities were observed with C. citratus treated groups of mice.